Determination of Scolytinae and Platypodinae (Coleoptera : Curculionidae) flight area using sticky traps - Paiola, Gabriel (2022)
The flight behavior and related aspects of Scolytinae and Platypodinae are poorly known and are commonly studied with baited flight intercept traps with different models and designs, with trapping varying between their models. We built an ethanol-baited sticky window trap with concentric circles that simulates different sizes of panels of intercept traps, to determine how accurately the targeted beetles can find the attractant source. The traps were positioned at different angles in relation to the predominant wind direction, to establish if the beetles fly upwind while searching for the attractant. The sticky window trap was not adequate to define if the Scolytinae, Platypodinae, Bostrichidae and Cerambycidae fly upwin trying to reach the attractant source. Most beetles were more trapped in the periphery of the trap, and the wind modeling indicated that the wind in both sides of the trap spread out, likely dragging the ethanol to the edges of the trap, hence changing the shape of the attractant plume. Keywords: Ambrosia beetles. Trap efficiency. Upwind flight. Wind modeling.